Static and dynamic magnetic properties and effect of surface chemistry on the morphology and crystallinity of DyCrO3 nanoplatelets - Gupta, Preeti; Bhargava, Richa; Das, Raja; Poddar, Pankaj (RSC Advances, 2013)
In this contribution, the structural and magnetic properties of DyCrO3 nanoplatelets, synthesized by a hydrolytic sol-gel method, have been investigated. The crystalline phase of DyCrO3 was attained at the decomposition temperature of 800 degrees C for citric acid and oxalic acid, respectively and their structural analysis indicates a distorted orthorhombic perovskite structure of the DyCrO3 nanoplatelets. The dc-magnetization curve shows the Neel temperature of similar to 144 and similar to 146 K for DyCrO3 nanoplatelets synthesized using citric acid (DCO (C)) and oxalic acid (DCO (O)), respectively. In addition, DCO (O) shows weak anomalies at similar to 22 and similar to 6 K in the zero-field-cooled and field-cooled magnetization curves. Below the Neel temperature, DCO (C) and DCO (O) exhibit cross-over from positive to negative magnetization at similar to 143 and similar to 145 K, respectively. This was attributed to a Dy3+-Cr3+ interaction, which resulted in a weak ferromagnetic coupling (seen as a small opening in the M-H curves). The low temperature transition observed at similar to 6 K can be assigned to the onset of Dy3+-Dy3+ antiferromagnetic interaction.

Synthesis, characterization and in vitro study of biocompatible cinnamaldehyde functionalized magnetite nanoparticles (CPGF Nps) for hyperthermia and drug delivery applications in breast cancer - Wani, Kirtee D.; Kadu, Brijesh S.; Mansara, Prakash; Gupta, Preeti; Deore, Avinash V.; Chikate, Rajeev C.; Poddar, Pankaj; Dhole, Sanjay D.; Kaul-Ghanekar, Ruchika (Plos One, 2014)
Cinnamaldehyde, the bioactive component of the spice cinnamon, and its derivatives have been shown to possess anticancer activity against various cancer cell lines. However, its hydrophobic nature invites attention for efficient drug delivery systems that would enhance the bioavailability of cinnamaldehyde without affecting its bioactivity. Here, we report the synthesis of stable aqueous suspension of cinnamaldehyde tagged Fe3O4 nanoparticles capped with glycine and pluronic polymer (CPGF NPs) for their potential application in drug delivery and hyperthermia in breast cancer. The monodispersed superparamagnetic NPs had an average particulate size of similar to 20 nm. TGA data revealed the drug payload of similar to 18%. Compared to the free cinnamaldehyde, CPGF NPs reduced the viability of breast cancer cell lines, MCF7 and MDAMB231, at lower doses of cinnamaldehyde suggesting its increased bioavailability and in turn its therapeutic efficacy in the cells. Interestingly, the NPs were non-toxic to the non-cancerous HEK293 and MCF10A cell lines compared to the free cinnamaldehyde. The novelty of CPGF nanoparticulate system was that it could induce cytotoxicity in both ER/PRpositive/Her2 negative (MCF7) and ER/PRnegative/Her2 negative (MDAMB231) breast cancer cells, the latter being insensitive to most of the chemotherapeutic drugs. The NPs decreased the growth of the breast cancer cells in a dose-dependent manner and altered their migration through reduction in MMP-2 expression. CPGF NPs also decreased the expression of VEGF, an important oncomarker of tumor angiogenesis. They induced apoptosis in breast cancer cells through loss of mitochondrial membrane potential and activation of caspase-3. Interestingly, upon exposure to the radiofrequency waves, the NPs heated up to 41.6 degrees C within 1 min, suggesting their promise as a magnetic hyperthermia agent. All these findings indicate that CPGF NPs prove to be potential nano-chemotherapeutic agents in breast cancer.

Study of magnetic and thermal properties of SmCrO3 polycrystallites - Gupta, Preeti; Poddar, Pankaj (RSC Advances, 2016)
In the present work, we have studied the magnetic and thermal properties of sol gel derived samarium chromite (SCO) polycrystallites. The magnetic measurements of SCO polycrystallites show a characteristic antiferromagnetic transition T-N similar to 190 K and spin reorientation temperature T-SR similar to 33 K, which is in the region of interest to study a possible magnetocaloric effect (MCE). The isothermal magnetic entropy change (Delta S-M) is estimated by an indirect method from the isothermal magnetization curves measured in this temperature range. The SCO polycrystallites possesses both inverse (positive) and normal (negative) MCE at and above around the spin reorientation transition (TSR) with Delta S-M(max) M values of similar to -24 x 10(-2) & 13 x 10(-2) J kg(-1) K-1, respectively. The SCO also shows another normal (negative) MCE peak around its Neel transition (T-N) with -Delta S-M(max) M similar to 11 x 10(-2) J kg(-1) K-1. The presence of two successive MCE peaks in SCO in the temperature range of 3-50 K, leads to an similar to 47 K operating temperature window with one thermodynamic cycle. In addition, the low temperature heat capacity (C-P) measurements of SCO polycrystallites reveal a lambda-shaped peak at T-N which is associated with a conventional second- order, paramagnetic to antiferromagnetic (AFM), phase transition. The temperature and magnetic field dependence of the specific heat capacity was studied and analyzed to estimate the adiabatic temperature change (Delta T-ad). In addition the C-P vs. T curve in SCO also shows a weak anomaly around the similar to T-SR along with a Schottky anomaly below 10 K.